Status of a Quality Management System in the Czech Republic as a Condition for Business Competitiveness - Kovářová, Kateřina (Vysoké učení technické v Brně, Fakulta podnikatelská, 2016)
Purpose of the article: Quality management systems are frequently used instruments for strategic management in business. Corporate management understands the importance of proving the quality of their products as well as other aspects, particularly environmental and safety issues in business connections and their possible negative impact on the company’s competitiveness and image. Methodology/methods: A data analysis was carried out based on a questionnaire research conducted in a selection group of Czech businesses with the objective to identify the reasons for introducing and using a management system, or to identify difficulties and problems in introducing it. The questionnaire research was statistically processed using analytic classification, hypotheses testing as well as a correlation analysis. The objective of the research was to validate or invalidate the hypotheses concerning the measures taken by a business in implementing and maintaining a quality management system (QMS), problems in its implementation, and to analyse competitive advantages and influence on the image. Findings: The research results confirmed that internal reasons for QMS implementation prevail in national businesses. Nevertheless, the main problem is the complexity of QMS/ understanding of the QMS by employees. An implemented QMS motivates the personnel, however, only a small number of enterprises use it to motivate their employees. The main benefits quoted by the respondents were improved company process management and relations between the processes, increased customer satisfaction as well as improved corporate image. Conclusions: A quality management system helps organisations to introduce system and order. Corporate processes are systematically managed, which significantly contributes to meeting the business objectives of a company. Having integrated the implemented QMS in their organisation, the respondents demonstrated they can effectively work with it and flexibly react to the changes faced in the present market environment.
Keywords: management; quality management system; process management; competitiveness; image